Pin1 Promotes NLRP3 Inflammasome Activation by Phosphorylation of p38 MAPK Pathway in Septic Shock - Dong, Ruijie; Xue, Zhenyi; Fan, Guangyue; Zhang, Na; Wang, Chengzhi; Li, Guangliang; Da, Yurong (Frontiers in Immunology, 2021)
Pin1 is the only known peptidyl-prolyl cis-trans isomerase (PPIase) that can specifically recognize and isomerize the phosphorylated Serine/Threonine-Proline (pSer/Thr-Pro) motif, change the conformation of proteins through protein phosphorylation, thus regulate various cellular processes in the body. Pin1 plays an important role in cancer, Alzheimer's disease, and autoimmune diseases. However, the specific mechanism of Pin1 regulation in LPS-induced septic shock is unclear. Here, we found that lack of Pin1 reduced shock mortality and organ damage in mice, and NLRP3 inflammasome activation also was reduced in this process. We further confirmed that Pin1 can affect the expression of NLRP3, ASC, Caspase1, and this process can be regulated through the p38 MAPK pathway. We analyzed that p38 MAPK signaling pathway was highly expressed in septic shock and showed a positive correlation with Pin1 in the Gene Expression Omnibus database. We found that Pin1 could affect the phosphorylation of p38 MAPK, have no obvious difference in extracellular signal-regulated kinases (ERK) and Jun-amino-terminal kinase (JNK) signaling. , We further found that Pin1 and p-p38 MAPK interacted, but not directly.We further found that Pin1 and p-p38 MAPK interacted, but not directly. In addition, Pin1 deficiency inhibited the cleavage of gasdermin D (GSDMD) and promoted the death of macrophages with LPS treatment, and reduced secretion of inflammatory cytokines including IL-1β and IL-18. In general, our results suggest that Pin1 regulates the NLRP3 inflammasome activation by p38 MAPK signaling pathway in macrophages. Thus, Pin1 may be a potential target for the treatment of inflammatory diseases such as septic shock.